Hemodynamic Instability Induced by Superselective Angiography of the Ophthalmic Artery - Stephan Klumpp; Lydia M. Jorge; Mohammed Ali Aziz-Sultan (Case Reports in Anesthesiology)
Retinoblastoma is one of the most common ophthalmic neoplasms affecting children worldwide. Since its recent introduction, superselective ophthalmic artery injection of chemotherapy with melphalan has significantly reduced the need for enucleation in patients with advanced disease and also shown to have minimal adverse effects on visual acuity as compared to the conventional therapy. Although no severe complications resulting in strokes or deaths have been reported, this treatment modality is not without difficulties. In this case discussion, we describe an event that has occurred to several pediatric patients undergoing superselective angiography of the ophthalmic artery that may be due to an oculopulmonary type reflex causing significant hemodynamic instability and hypoxemia.